Isolation and Characterization of Cellulolytic Bacteria During Natural Fermentation of Sweet Orange Peel Waste (Citrus sinensis) - La Ode Sumarlin; Farida Ariyanti; Megga Ratnasari Pikoli; Anna Muawanah; Meyliana Wulandari (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2022)
Abstract Orange peel is one of organic waste which contains fibers, such as cellulose and hemicellulose utilized by cellulolytic microorganisms as growth media in the fermentation process. Cellulolytic microorganisms are widely used in many industries. This research will observe the profile of bacterial colonies, particularly cellulosic bacteria, during the fermentation of orange peels (Citrus sinensis). Fermentation was carried out during the research process; the bacteria were further isolated in Carboxymethyl Cellulose (CMC) media. The fermentation process was performed for 14 weeks where sampling on the first week was done every day for five days (H0–H4), while sampling from the 2nd to 14th weeks were conducted once a week (M2–M14). The isolation process was carried out in a Nutrient Agar medium with spreading method by calculating the Total Plate Count (TPC) of bacterial colonies and observing the macroscopic morphology of bacterial colonies. Bacterial counts are expressed in Colony Forming Units (CFU)/mL or viable count/mL. The identification of bacterial genus was based on the Bergey's Manual of Determinative Bacteriology. Bacterial isolation from the fermentation of sweet orange peel resulted in 20 isolates where 16 isolates were found to be cellulolytic bacteria through qualitative test in Carboxymethyl Cellulose (CMC) agar plate. The hypothetic genus of 16 bacterial isolates were Eubacterium, Cellulomonas, Microbacterium, Micrococcus, Planococcus, Pseudomonas, Azotobacter, Azomonas, Flavobacterium, Cytophaga, and Jonesia. Isolate F15 (Cytophaga and Azomonas) was found to dominate the growth, while other isolates grew alternately with lesser frequency. Hypothetic genus of bacteria actively involved in the process were cellulolytic bacteria, allowing the liquid of fermentation products to be possibly used in the application.AbstrakKulit jeruk merupakan salah satu limbah organik yang mengandung serat seperti selulosa dan hemiselulosa yang dapat dimanfaatkan oleh mikroorganisme selulolitik sebagai media pertumbuhan dalam proses fermentasi. Mikroorganisme selulolitik telah digunakan di banyak industri. Penelitian ini mengamati profil koloni bakteri selama proses fermentasi kulit jeruk terutama bakteri selulotik. Selama proses penelitian dilakukan proses fermentasi, lalu bakteri diisolasi menggunakan media Carboxyl Methyl Callulose (CMC). Proses fermentasi dilakukan selama 14 minggu dengan rincian sampling pada Minggu ke-1 dilakukan setiap hari selama 5 hari (H0–H4), sedangkan minggu ke-2 hingga 14 dilakukan setiap seminggu sekali (M2–M14). Proses isolasi dilakukan dalam medium Nutrient Agar dengan teknik sebar dengan perhitungan koloni Total Plate Count (TPC) dan pengamatan morfologi koloni bakteri secara makroskopis. Hasil perhitungan bakteri dinyatakan dalam Colony Forming Units (CFU)/mL atau viabel count/mL. Pendugaan genus bakteri berdasarkan Bergey's Manual of Determinative Bacteriology. Hasil isolasi bakteri dari fermentasi kulit jeruk manis adalah 20 isolat yang 16 di antaranya merupakan bakteri selulolitik melalui uji kualitatif pada media plat Carboxymethyl Cellulose (CMC). Genus hipotetik bakteri dari 16 isolat adalah Eubacterium, Cellulomonas, Microbacterium, Micrococcus, Planococcus, Pseudomonas, Azotobacter, Azomonas, Flavobacterium, Cytophaga, dan Jonesia. Isolat F15 (Cytophaga dan Azomonas) mendominasi pertumbuhan, sedangkan isolat lain tumbuh berselang seling dengan frekuensi yang lebih kecil. Genus bakteri hipotetik yang terlibat aktif adalah bakteri selulolitik sehingga cairan hasil fermentasi dapat digunakan dalam aplikasi.